Review of the Fund's Income Position for FY 2016 and FY 2017-2018. (Policy Papers; Policy Paper ;, 2016)
The Fund's total net income for FY 2016 including surcharges is projected at about SDR 1.0 billion or some SDR 0.15 billion higher than expected in April 2015. Lending income continues to be the main source of income and is in line with April 2015 estimates. Investment income has fallen reflecting the decline in equity markets that exceeded the modest returns on fixed income securities. As a result of the 5-yearly review of key actuarial assumptions, the IAS 19 adjustment (relating to reporting of employee benefits) is expected to contribute about SDR 0.3 billion to net income in FY 2016. The paper recommends that GRA net income of SDR 1.1 billion for FY 2016 (which excludes projected losses of the gold endowment), be placed equally to the special and general reserve. After the placement to reserves, precautionary balances are projected to reach SDR 15.2 billion at the end of FY 2016. Following the completion of the Board's review of the investment strategy for the Fixed-Income Subaccount, the paper further proposes to transfer currencies equivalent to the increase of the Fund's reserves for FY 2014 and FY 2015 (totaling SDR 2.6 billion) and FY 2016 (estimated at SDR 1.1 billion), from the GRA to the Investment Account. The paper proposes that the margin for the rate of charge be set at 100 basis points for the two years FY 2017 and FY 2018. This follows a comprehensive review of the underlying factors relevant for the establishment of the margin this year and also takes into account the impact of the inclusion of the renminbi in the SDR basket on Fund income and borrowing costs. The projections for FY 2017 and FY 2018 point to a net income position of SDR 1 billion and SDR 0.7 billion, respectively. These projections are subject to considerable uncertainty and are sensitive to a number of assumptions.